Oligocene-Miocene drainage evolution of NW Borneo: Stratigraphy, sedimentology and provenance of Tatau-Nyalau province sediments. (15th June 2020) - Breitfeld, H. Tim; Hennig-Breitfeld, Juliane; BouDagher-Fadel, Marcelle K.; Hall, Robert; Galin, Thomson
Graphical abstract: Highlights: Tatau-Nyalau province is sourced predominantly by the Sunda River system. Sediments of the Sunda River are dominated by Permo-Triassic & Precambrian zircons. Proto-Rajang sediments are characterised by a higher amount of Cretaceous zircons. Source areas are East Malaya for the Sunda River and Borneo for the proto-Rajang. Nyalau Unconformity marks a change in sediment provenance and coastline orientation. Abstract: Clastic sediments of Oligocene to Lower Miocene age form a major thick and widespread sequence in the Tatau-Nyalau province of the north Sarawak Miri Zone. New light and heavy mineral data, U-Pb detrital zircon geochronology and biostratigraphy are used to identify the age, depositional environment, and potential provenance of sediments to reconstruct the drainage evolution of NW Borneo. Based on the biostratigraphic ages, depositional environments and provenance characteristics we modify previous stratigraphy and divide the Oligocene to Lower Miocene sequences into the Nyalau Formation (Biban Sandstone Member and Upper Nyalau Member), Kakus Unit, and Merit-Pila Formation. Two dominant source provinces were identified: the Malay-Thai Tin Belt which supplied sediments dominated by Permian-Triassic zircons, and the Schwaner Mountains of central Borneo which are identified by abundant Cretaceous zircons. Sediments either came directly, or were recycled from older sedimentary rocks, from these sources. The Sunda River deposited the Nyalau Formation during the Oligocene to Early Miocene with a dominant Malay-Thai Tin Belt source. The Merit-Pila Formation of the Sibu Zone was deposited contemporaneously by a proto-Rajang River that drained Central Borneo (recycling the Rajang Group and Schwaner granitoids). Between c. 17 Ma the Sunda River system terminated and sedimentation was dominated by the northward prograding proto-Rajang River delta, depositing the Kakus Unit in the Miri Zone. This drainage system was active until the Late Miocene, before further uplift of Borneo terminated most sedimentation in the onshore part of present-day Borneo.